Sustainability and environmental issues / Hamimah Adnan, Mohd. Nidzam Rahmat and Abdul Hadi Nawawi - Adnan, Hamimah; Rahmat, Mohd. Nidzam; Nawawi, Abdul Hadi (UiTM Press, 2008)
There is an increasing demand, in both the private and public sectors, to understand sustainable construction practices. This demand is driven by a realization that sustainable practices make sense to both owners and operators. The practices not only help the environment but can also improve economic profitability and improve relationships with stakeholder groups. The strategy and practices for more sustainable construction is a significant milestone on the road to a more socially and environmentally responsible, better-regarded construction industry. It provides a framework within which the industry can make a strong contribution to the better quality of life signaled by our sustainable development strategy